The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000374110
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data and Dialectical Effects on Nasalance in Flemish Adults

Abstract: Objective: The purpose of this study was to investigate the impact of dialect and gender and to obtain normative nasalance values for Flemish adults as measured with the Nasometer II. Subjects and Methods: One hundred and sixty-four adult subjects from the five regions in Flanders corresponding to different dialects were included in the study. The group consisted of 71 adult men and 93 adult women with a mean age of 43 years and an age range between 20 and 82 years (SD 16). Nasalance scores of connected speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…A study conducted in Greece (24) , which evaluated 80 healthy young adults (40 males and 40 females) monolingual speakers of Greek, showed that, in addition to the fact that no significant difference was found between genders, Greek obtained lower nasalance scores than other languages examined in previous surveys. In a study conducted in Belgium, which evaluated the influence of gender and the effects of five different dialects of Flemish on nasalance, no statistically significant differences were found (26) .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…A study conducted in Greece (24) , which evaluated 80 healthy young adults (40 males and 40 females) monolingual speakers of Greek, showed that, in addition to the fact that no significant difference was found between genders, Greek obtained lower nasalance scores than other languages examined in previous surveys. In a study conducted in Belgium, which evaluated the influence of gender and the effects of five different dialects of Flemish on nasalance, no statistically significant differences were found (26) .…”
Section: Discussionmentioning
confidence: 95%
“…Dialectal influence on nasalance scores has been investigated by several authors worldwide; however, whereas some authors have found differences between the dialects investigated (15,24,25) , others have reported that this is not a significant factor (13,14,20,26) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations